2013
DOI: 10.1080/14786419.2012.750316
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of alkaloids produced by endophytic fungusAspergillussp. EJC08 isolated from medical plantBauhinia guianensis

Abstract: Bauhinia guianensis is a typical plant in the Amazon region belonging to the family Leguminosea, used by local populations for the treatment of infectious and renal diseases. Previous work on the plant B. guianensis led to the isolation of substances with anti-inflammatory and analgesic activities. Thus, compounds isolated from B. guianensis with antimicrobial activities had not been identified. Given that there is a possibility of biological activity reported for a given plant being found in the endophytic fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 13 publications
2
44
1
5
Order By: Relevance
“…B 371: 20160023 BGC 6 (Fumigaclavine). Fumigaclavines are bioactive alkaloids with numerous bioactivities ranging from antibacterial [52] to vasorelaxant [53]. Fumigaclavines are considered mycotoxins and purified compounds have a toxic impact on mammalian cells [54].…”
Section: Results and Discussion (A) Twenty-six Clustersmentioning
confidence: 99%
“…B 371: 20160023 BGC 6 (Fumigaclavine). Fumigaclavines are bioactive alkaloids with numerous bioactivities ranging from antibacterial [52] to vasorelaxant [53]. Fumigaclavines are considered mycotoxins and purified compounds have a toxic impact on mammalian cells [54].…”
Section: Results and Discussion (A) Twenty-six Clustersmentioning
confidence: 99%
“…New species, useful for biotechnology applications, have been reported to produce extracellular active metabolites with pharmacological interest (Bagchi and Banerjee, 2013;Pinheiro et al, 2013). These microorganisms can also protect plants against phytopathogens, temperature, drought and world weather changes (Gundel et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that endophytic fungi can produce numerous compounds with biological activities of interest, such as antitumor (Jin-long et al, 2011;Chandra, 2012), antimicrobial (Siqueira et al, 2011;Tayung et al, 2012;Bagchi and Banerjee, 2013;Pinheiro et al, 2013;Orlandelli et al, 2015), enzymes (Chandra, 2012), plant growth hormones (Hwang et al, 2011), leishmanicidal (Santiago et al, 2012), cytotoxic compounds and compounds with industrial and pharmaceutical potential (Meng et al, 2011;Wang and Dai, 2011), reinforcing the broad biotechnological potential of these microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Both are broad-spectrum antibacterial agents, however, fumigaclavine C was the most active against B. subtilis showing MIC of 7.81 mg/ml, while pseurotin showed MIC 15.62 mg/ ml. [49] The mangrove endophyte Aspergillus sp. 16-5c produced a sesterterpenoid, asperterpenoid A (60).…”
Section: Endophyte-host Interactionmentioning
confidence: 99%